A Study of the Librarians\' General and Specialized Reading Status at Mashhad Public Libraries - Mohammad Zerehsaz; Fatemeh Pazooki (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2012)
Purpose: This study aims to determine the status of the librarians' general and specialized reading at Mashhad public libraries and identify the factors which impact it. Method: A descriptive analytical method was used as the research method. A researcher-made questionnaire was selected as the tool for data collection. Findings: According to the librarians, the average time they spend a day on general and specialized reading is respectively 47.77 and 29.08 minutes. The findings showed that the librarians' interest in general reading is higher than an intermediate level while their specialized reading is lower than an average level. Increasing general information, learning to enjoy by reading, and responding to the library clients have been the most important reasons reported by the librarians for their general reading. However, the most important reasons for their specialized reading have emerged to be increasing their ability to respond to the clients, being up-to-date and active participation in scientific communities. Tiredness resulting from daily work, ineffectiveness of reading in job evaluation, and administrative rules have been the major obstacles reported by the librarians for specialized reading. Findings also indicated a significant negative correlation between the librarians' age and their general and specialized reading. Originality/Value: This study has documented the reading status of librarians of Mashhad public libraries and identified some existing challenges and problems. In case they are solved and systematic plans are adopted by managers, qualified librarians and information consultants may be trained for public libraries